Analysis of the surface quality of a convex machining for a martensitic steel AISI P20. (2022) - Juiña, Luis Christian; Dávalos, Emilio Josué; Pilataxi, Erika; Pillajo, Oscar; Cabrera, Victor; Moreno, Nancy Verónica
Abstract: The purpose of this research project is to generate an algorithm that allows predicting roughness, an important factor for measuring the surface finish of machined parts and thus establishing adequate machining parameters that have an impact on manufacturing cost time. The research carried out uses analysis of experiments based on the ANOVA and Taguchi methodology, the data were generated from tests carried out in a machine with computerized numerical control on specimens of AISI P20 martensitic steel material, the machining process was carried out on a convex surface with the application of finishing strategies arranged in a CAM software, there were 27 tests, with ZIGZAG, ZIGZAG Concentric and ZIGZAG RADIAL strategies, with cutting speed between 70 and 110 m/min and a feed per tooth that varies from 0.05 to 0.15 [mm/tooth]. With the analysis of the data, the following equation Ra = 2.1720–0.2829A + 0.6417C is generated, where A is the strategy and C the advance, the validation of the algorithm was carried out by contrasting the theoretical value of 1.335 [µm] and the value measured in the specimen of 1.311 with an error of 3.4% between the 2 values. By having the algorithm validated, it is possible to establish a desired roughness and verify machining times and their impact on the final cost of the product.